Data Driven and Sustainable Innovation Strategies for Long Term Product Market Fit in SMEs - Sri Lestari Pujiastuti; Nanda Septiani; Adam Faturahman; Steven Harazaki Lase; Mitra Trima Dessincer Putri; April Lansonia (APTISI Transactions on Management (ATM), 2026)
In an increasingly dynamic and sustainability-conscious marketplace, startups and SMEs face mounting pressure to sustain product relevance and strategic resilience over time. This study investigates how integrated data-driven strategies support long-term product–market fit (PMF) through the alignment of real-time analytics, structured customer feedback loops, and sustainability-oriented innovation practices. Drawing on Resource-Based and Organizational Capability perspectives, the study conceptualizes digital capability formation as a strategic asset that strengthens adaptive market alignment under structural constraints. Using PLS-SEM analysis on data collected from 110 SMEs, five key constructs are examined: technology utilization, data-driven decision-making, customer feedback integration, sustainable innovation capability, and market responsiveness. The results indicate that technology utilization and data-driven decision-making exert significant positive effects on long-term PMF, while customer feedback integration facilitates iterative product refinement and market consistency. However, sustainable innovation capability and market responsiveness demonstrate negative path coefficients, suggesting that without structured governance, digital maturity, and prioritization mechanisms, these capabilities may generate operational strain or reactive strategic behavior that weakens long-term positioning. The findings extend the Data Strategy–Sustainability convergence literature by validating an integrative model that bridges digital capability development and responsible innovation in SME contexts. Managerially, the study highlights the importance of phased digital adoption and disciplined sustainability integration to ensure durable competitive alignment within evolving industrial ecosystems